Urban development for the 21st century managing resources and creating infrastructure - Etingoff, Kimberly (Apple Academic Press Inc., 2015)
Urban planners around the world are increasingly concerned with creating and maintaining cities that are healthy for both the environment and for individuals. Cities are at the forefront of the trend toward sustainable living, since they are the site of concentrated population, resource use, and greenhouse gas emissions, yet also have the tools and the resources to address climate change and environmental degradation. Part of the modern urban planner's challenge is to impact individual behavior on a systemic, urban scale, since sustainable cities are made up of systems that encourage sustainable behavior